2011
DOI: 10.1161/circgenetics.110.958298
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Early Repolarization

Abstract: Background-Early repolarization (ER), defined by J-point elevation in 12-lead ECG, was recently associated with increased risk for idiopathic ventricular fibrillation and cardiovascular mortality. The determinants of ER are unknown. We investigated its heritability in a large, family-based cohort. Methods and Results-The study sample comprised 1877 individuals from 505 white nuclear families representative of the British general population. Standard 12-lead ECGs were evaluated for the presence of ER, defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 31 publications
2
56
0
1
Order By: Relevance
“…A study involving 505 Caucasian nuclear families reported that individuals with ≥1 parent with ER had a 2.5-fold increased incidence of demonstrating the ER pattern. 50 Familial transmission appeared more frequent when the mother was affected (3.8-fold versus 1.8-fold, P=0.1). Potential explanations for unequal transmission include transmission through mitochondrial DNA, effects mediated via sex chromosomes, and parental imprinting of autosomal genes.…”
Section: Inheritance Of Early Repolarization and Family Screeningmentioning
confidence: 95%
See 1 more Smart Citation
“…A study involving 505 Caucasian nuclear families reported that individuals with ≥1 parent with ER had a 2.5-fold increased incidence of demonstrating the ER pattern. 50 Familial transmission appeared more frequent when the mother was affected (3.8-fold versus 1.8-fold, P=0.1). Potential explanations for unequal transmission include transmission through mitochondrial DNA, effects mediated via sex chromosomes, and parental imprinting of autosomal genes.…”
Section: Inheritance Of Early Repolarization and Family Screeningmentioning
confidence: 95%
“…25,50 In 2 large population-based cohorts, 25 siblings of individuals with ER had an increased unadjusted odds of ER (odds ratio, 2.22; P=0.047). A study involving 505 Caucasian nuclear families reported that individuals with ≥1 parent with ER had a 2.5-fold increased incidence of demonstrating the ER pattern.…”
Section: Inheritance Of Early Repolarization and Family Screeningmentioning
confidence: 99%
“…Although this definition differs slightly from a recent consensus document, 21 it is in keeping with that used by Tikkanen et al 17 when first demonstrating the prognostic benefit of ST-segment gradient. Similar criteria, described previously, 6 were used for the control population. J-point amplitude was categorized in 0.1 mV increments (ie, 0.10-0.19 mV; 0.20-0.29 mV, etc) and considered high amplitude if ≥0.2 mV.…”
Section: Ecg Analysismentioning
confidence: 99%
“…3 In addition, there is increasing evidence for the role of ER as a risk factor for arrhythmic events in the context of other inherited arrhythmia syndromes. 4,5 Several studies have suggested the ER pattern is a heritable phenotype 6,7 and variants in genes encoding cardiac ion channels [8][9][10] have been identified in individuals and families with ERS.…”
mentioning
confidence: 99%
“…
We read with much interest the article published by Reinhard et al 1 The article described a high rate of heritability of early repolarization (ER) in a general population. Early repolarization was characterized by ECG morphological features of the QRS complex (ie, notching, slurring, or both).
…”
mentioning
confidence: 99%